Aumento de la actividad fagocítica de macrófagos usando extracto acuoso de aloe vera frente a staphylococcus aureus en rattus norvegicus - Horna García, Oscar Aarón (2017)
The increase of the bacterial resistance product of the indiscriminate use of antibiotics, motivates us to look for long-term alternatives that allow to avoid the advance of the microorganisms, because this way the present study tried to verify the increase of the phagocytic activity of macrophages by the extract aqueous of Aloe vera against Staphylococcus aureus in Rattus norvegicus. Materials and methods: The extraction method of Alvarez et al. Was used, collecting plants from 1 to 2 years of age, keeping at 4 ° C in a dark place and separating the gel when removing the edges, preparing the aqueous extract when centrifuging. and let rest by removing the insultible remains. The inoculation of a 0.5mL solution of Staphylococcus aureus and a control group was inoculated with 0.5mL of saline solution and the 0.5ml of the A.vera extract was inoculated, and the specimens were later sacrificed. perform a peritoneal smear to count on plate. Results: Average of 14 phagosomes per phagocyte in the control group and 23 phagosomes per phagocyte in the experimental group, there being a significant difference verified by hypothesis test. Conclusion: There are significant increases in the phagocytic activity of macrophages by the aqueous extract of Aloe vera against Staphylococcus aureus in Rattus norvegicus